Multifunctional porous silicon nanoparticles for cancer theranostics - Wang, Chang-Fang; Sarparanta, Mirkka P.; Mäkilä, Ermei M.; Hyvönen, Maija L.K.; Laakkonen, Pirjo M.; Salonen, Jarno J.; Hirvonen, Jouni T.; Airaksinen, Anu J.; Santos, Hélder A. (Biomaterials, 2015)
Nanomaterials provide a unique platform for the development of theranostic systems that combine diagnostic imaging modalities with a therapeutic payload in a single probe. In this work, dual-labeled iRGD-modified multifunctional porous silicon nanoparticles (PSi NPs) were prepared from dibenzocyclooctyl (DBCO) modified PSi NPs by strain-promoted azide-alkyne cycloaddition (SPAAC) click chemistry. Hydrophobic antiangiogenic drug, sorafenib, was loaded into the modified PSi NPs to enhance the drug dissolution rate and improve cancer therapy. Radiolabeling of the developed system with 111In enabled the monitoring of the in vivo biodistribution of the nanocarrier by single photon emission computed tomography (SPECT) in an ectopic PC3-MM2 mouse xenograft model. Fluorescent labeling with Alexa Fluor 488 was used to determine the long-term biodistribution of the nanocarrier by immunofluorescence at the tissue level ex vivo. Modification of the PSi NPs with an iRGD peptide enhanced the tumor uptake of the NPs when administered intravenously. After intratumoral delivery the NPs were retained in the tumor, resulting in efficient tumor growth suppression with particle-loaded sorafenib compared to the free drug. The presented multifunctional PSi NPs highlight the utility of constructing a theranostic nanosystems for simultaneous investigations of the in vivo behavior of the nanocarriers and their drug delivery efficiency, facilitating the selection of the most promising materials for further NP development.